Rubber-Toughened Polypropylene Nanocomposite: Effect of Polyethylene Octene Copolymer on Mechanical Properties and Phase Morphology - Lim, J. W.; Hassan, A.; Rahmat, A. R.; Wahit, M. U. (Wiley Company, 2006)
Rubber-toughened polypropylene (PP)/org-Montmorillonite (org-MMT) nanocomposite with polyethylene octene (POE) copolymer were compounded in a twinscrew extruder at 230°C and injection-molded. The POE used had 25 wt % 1-octene content and the weight fraction of POE in the blend was varied in the range of 0–20 wt %. X-ray diffraction analysis (XRD) revealed that an intercalation org-MMT silicate layer structure was formed in rubber toughened polypropylene nanocomposites (RTPPNC). Izod impact measurements indicated that the addition of POE led to a significant improvement in the impact strength of the RTPPNC, from 6.2 kJ/m2 in untoughened PP nanocomposites to 17.8 kJ/m2 in RTPPNC containing 20 wt % POE. This shows that the POE elastomer was very effective in converting brittle PP nanocomposites into tough nanocomposites. However, the Young’s modulus, tensile strength, flexural modulus, and flexural strength of the blends decreased with respect to the PP nanocomposites, as the weight fraction of POE was increased to 20 wt %. Scanning electron microscopy (SEM) was used for the investigation of the phase morphology and rubber particles size. SEM study revealed a two-phase morphology where POE, as droplets was dispersed finely and uniformly in the PP matrix